Psychological and Cultural Factors: Does an Accounting Study Program Matter? - Frista Fio Amanda; Zaky Machmuddah (Universitas Dian Nuswantoro, 2025)
ABSTRACT The phenomenon of declining interest in accounting study programs has become a significant issue in Indonesian higher education. This study aims to analyze the influence of psychological, social, and cultural factors on students decisions to major in accounting at university